Description Of Long Covid-19 Patients With Symptoms Of Anosmia And Agnosia At Gatot Soebroto Hospital And According To The Islamic Perspective - Chairu Silaturrachmi Anzali; Yenni Zulhamidah; Muhammad Arsyad (Junior Medical Journal, 2022)
Background : Long COVID is a term used to describe the presence of various symptoms that continue even weeks or months after contracting a SARS-CoV-2 infection regardless of viral status. Anosmia is the inability of the nose to taste or smell. Agnosia is defined as a partial or complete inability to recognize sensory stimuli. In Islam we are taught that if we are experiencing or facing various kinds of tests, one example is like the COVID-19 pandemic, we must remain patient, keep our trust in Allah SWT. Apart from that, we must also remain grateful to Allah SWT even though we are being hit by a pandemic, because health is one of the blessings from Allah SWT which we must be grateful for. Purpose: The purpose of this study was to determine the picture of long COVID-19 patients with symptoms of anosmia and agnosia at Gatot Soebroto Hospital and based from an Islamic perspective.Method: This research uses a descriptive type of research with a retrospective method. The population in this study was long COVID-19 patients at Gatot Soebroto Hospital in 2021 with symptoms of anosmia and agnosia. Data analysis is carried out by univariate analysis.Result: Of the 142 medical record data of patients who had COVID-19 who had symptoms of anosmia and agnosia totaled 10 patients, and those who continued to be long COVID-19 with symptoms of anosmia totaled 3 people while for agnosia symptoms there were none.Conclusion: The age and gender description of long COVID-19 patients with anosmia symptoms is that there are more patients of the female sex and for the most age spanning the age of 20-30 years, but for agnosia symptoms there is none. In Islam we are taught that if we are experiencing or facing various kinds of life lesson, for example like the COVID-19 pandemic, we must remain patient, keep our trust in Allah SWT.